A Training-Model Scale’s Validity and Reliability Coefficients: Expert Evaluation in Indonesian Professional Psychology Programs - Ningdyah, Anrilia E. M.; Greenwood, Kenneth Mark; Kidd, Garry (UI Scholars Hub, 2018)
Very little information has been available on training models in professional psychology programs in Indonesia, despite the IndonesianNational Accreditation Body recommending that scientist-practitioner models be applied in the education of psychologists. By contrast, research abounds on such training models in Western countries. This discrepancy raises the importance of developing a measurement tool appropriate for assessing training models in Indonesian professional psychology programs. This article describes the process of testing the validity and reliability of such a training model measuring tool in the Indonesian context. The authors used the expert evaluation method and the Aiken formula to calculate a coefficient of content validity and item’s internal consistency reliability. This process formed a training model scale comprising 77 items with satisfactory validity and reliability indexes for measuringIndonesian professional psychology program training models.